Regulatory dilemma: a changing dynamics of the Cochin international airport. Issue 3 (16th August 2021) - Damodaran, Akhil; Dhingra, Tarun; Dwivedi, Prasoom
Abstract : Learning outcomes: The case study helps students to understand how public-private partnership (PPP) airports runs their business, how regulatory policies impact their business. The case also explains why the Cochin International Airport business model is so unique compared to any airport in India. Case overview/synopsis: In 2016, Airport Economic Regulatory Authority released a new tariff regime for Cochin International Airport Limited (CIAL).CIAL has undergone challenges because of the tariff changes (changes every five years), which were implemented in 2017. This has impacted their business model. The CFO of CIAL was under pressure to share the impacts with the shareholders and to provide a way forward for the business. Cochin International was known to be one of the cheapest aeronautical tariff charging airports. The case discusses the issues of a public utility when it is under a regulatory price regime. The case explains different regulatory mechanisms (single till: the whole commercial revenue is cross-subsidized). The case discusses issues regarding Cochin International Airport, which is a public utility under PPP mode. Since 2016, regulator has changed the price regulatory regime from light touch (no price regulation only monitoring) to hybrid till regulation (a percentage of commercial revenue is cross-subsidized). The case explains what made Cochin International Airport so unique. It explores the challenges because of the regulatory regime, how it affects Cochin airport's strategy for business. How should the management of CIAL to act on the above issue? What will be the impact? Will they need to change their business models? Complexity academic level: The case is basically focused on MBA level students who are in their final year. There are various MBA courses in which this can be taught, which can be infrastructure management, infrastructure regulation, domain courses such as airport management. The student should have basic knowledge of economics, public utility and business strategy. The case helps them understand the impact of regulation, the role of the regulator and its impact on business strategy. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS: 10 Public Sector Management.